2015
DOI: 10.1097/iio.0000000000000083
|View full text |Cite
|
Sign up to set email alerts
|

External Versus Endoscopic Endonasal Dacryocystorhinostomy

Abstract: DCR is the treatment of choice for NLDO. External DCR has remained the standard approach since the 1890s. With advances in technique and technology, and more otolaryngologists and ophthalmologists performing endoscopic DCR, more studies have been conducted, some with equivalent success rates between the 2 approaches. Endoscopic endonasal DCR offers the advantages of avoiding a skin incision with similar success rates with experienced surgeons. However, the technique necessitates more surgical equipment, and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
(68 reference statements)
0
17
0
Order By: Relevance
“…The purpose of this surgery is to create a fistula between the lacrimal sac and the nasal cavity. Thus, the tear will flow directly from the lacrimal sac to the nasal cavity without using the lacrimal duct (1). Traditional external or transcutaneous DCR was first described by Toti, and endoscopic DCR (END-DCR), which is an alternative to external DCR (EXT-DCR), was described by Caldwell.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The purpose of this surgery is to create a fistula between the lacrimal sac and the nasal cavity. Thus, the tear will flow directly from the lacrimal sac to the nasal cavity without using the lacrimal duct (1). Traditional external or transcutaneous DCR was first described by Toti, and endoscopic DCR (END-DCR), which is an alternative to external DCR (EXT-DCR), was described by Caldwell.…”
Section: Introductionmentioning
confidence: 99%
“…In studies, the rate of success was reported as 80 to 95% (4-7) for EXT-DCR and 60 to 99% (8)(9)(10) for END-DCR. The most important concern of patients with EXT-DCR is the formation of scars on the skin (1). The supporters of END-DCR argue that no scar is formed on the skin and that the pumping function is preserved (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al also reported that among 554 external DCR procedures performed, it was found that 10.8% of patients reported an unacceptable scar [15]. Proponents of the endonasal endoscopic technique cite the obvious benefits of no skin incision and precluding a scar [15,18]. The other often cited advantages of endoscopic DCR include being less surgically invasive, a shorter operative time, preservation of the lacrimal pump and faster postoperative rehabilitation [19].…”
Section: Endoscopic Vs External Dacryocystorhinostomy: Which Has a Bmentioning
confidence: 99%
“…Despite the emergence of new techniques such as endoscopic DCR, external DCR is still the criterion standard in primary cases, with a success rate of 80-95%. 1…”
Section: Introductionmentioning
confidence: 99%